Acute procedural characteristics, efficacy, and safety of a novel cryoballoon for the treatment of paroxysmal atrial fibrillation: Results from the POLAR-ICE study. (19th May 2022) - Tilz, R; Martin, CA; Anic, A; Defaye, P; Luik, A; Asmundis, C; Champ-Rigot, L; Iacopino, S; Sommer, P; Albrecht, E; Raybuck, JD; Wehrenberg, S; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Private company. Main funding source(s): Boston Scientific Background/Introduction: Pulmonary vein isolation (PVI) using a cryoballoon is well-established for the treatment of paroxysmal atrial fibrillation (PAF). Initial experience with a novel cryoballoon (CB) with a stable low balloon pressure (POLARx, Boston Scientific) has demonstrated acute procedural safety and efficacy in de novo PVI procedures in patients with paroxysmal AF. However, to date, there is limited multicenter data on real world acute outcomes and procedural characteristics with this novel cryoballoon. Purpose: The purpose of POLAR ICE was to provide real-world data on the acute and chronic outcomes of cryoballoon ablation with POLARx for the treatment of PAF. Here we report on the initial acute outcomes up to 3 months including procedural efficacy, safety, and biophysical parameters. Methods: POLAR ICE, a prospective, non-randomized, multicenter (international) registry (NCT04250714), enrolled 400 patients across 19 centers, between Aug 2020 and May 2021. This study included any patients indicated for treatment of PAF with the POLARx cryoablation system. The study protocol did not mandate any specific cryodosing regimen, this was left to the operator. Procedural characteristics, such as time to isolation (TTI), cryoablations per pulmonary vein, balloon nadir temperature, and occlusion grade were recorded. PVI was confirmed with entrance block testing. Results: Complete PVI was achieved in 96.1% of PVs (1437/1496). Procedure and fluoroscopy times were 69.0±25.2 min and 15.8±10.0 min, respectively. Left atrial dwell time was 47.3±18.8 min. The cryoablation characteristics by vein are shown in the Table 1. An average of 4.9±1.8 ablations were performed per patient (1.3±0.7 per vein). Grade 3 or 4 occlusion was achieved in 98.1% of PVs reported. Electrical isolation was achieved with an average TTI of 50±33.8s and in 81.4% of PVs isolation required only a single cryoablation. Nadir temperatures across all pulmonary veins averaged -56.3± 6.5C. Time to -40C was 32.9±11s and Time to Thaw (0C) was 19.5±6.7s across all veins. PVI was performed on atypical anatomies (12 LCPV, 7 RMPV, & 3 RCPV) in 19 pts. Serious adverse events included phrenic nerve palsy (0.5%), tamponade (0.5%), AV block (0.3%), stroke (0.3%), and transient ischemic attack (0.3%). Conclusions: Real world usage data on the novel CB suggests that this device is safe and effective, with a PV isolation success rate of 96.2% and 81.4% of PVs isolated with a single cryoablation. These data are in keeping with reports on other cryoballon systems and have markedly shorter procedure times than have been previously reported on this cryoballon.